2021
DOI: 10.1038/s41398-021-01664-5
|View full text |Cite
|
Sign up to set email alerts
|

The proteomic architecture of schizophrenia iPSC-derived cerebral organoids reveals alterations in GWAS and neuronal development factors

Abstract: Schizophrenia (Scz) is a brain disorder that has a typical onset in early adulthood but otherwise maintains unknown disease origins. Unfortunately, little progress has been made in understanding the molecular mechanisms underlying neurodevelopment of Scz due to ethical and technical limitations in accessing developing human brain tissue. To overcome this challenge, we have previously utilized patient-derived Induced Pluripotent Stem Cells (iPSCs) to generate self-developing, self-maturating, and self-organizin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 93 publications
3
20
0
Order By: Relevance
“…Schizophrenia organoids were also subjected to quantitative proteomic analysis. Similar defects were observed in axon and neuronal differentiation at protein level (Notaras et al, 2021b), which is consistent with transcriptome and genome researches.…”
Section: Brain Organoids Reveal the Genetic Mechanism Of Neural Diseasessupporting
confidence: 89%
“…Schizophrenia organoids were also subjected to quantitative proteomic analysis. Similar defects were observed in axon and neuronal differentiation at protein level (Notaras et al, 2021b), which is consistent with transcriptome and genome researches.…”
Section: Brain Organoids Reveal the Genetic Mechanism Of Neural Diseasessupporting
confidence: 89%
“…3e) and downregulation of genes such as CRABP1, POU3F2 and NOVA1 (Fig. 3f) whose dysregulation was linked to the SCZ risk [50-53]. Gene ontology (GO) analysis identified the remarkable upregulation of synaptic transmission-related genes and downregulation of genes regulating translation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notaras et al observed that in SZ BO, about 2.62% of global proteome was differentially regulated, with a depletion of factors that support neuronal development, differentiation, and/or function [ 48 ]. Moreover, the differential regulation of two novel specific disease candidates identified through genome-wide association study (GWAS) arrays (namely, Pleiotrophin and Podocalyxin) was observed [ 48 ]. The SZ organoids exhibited altered progenitor survival and disrupted neurogenesis, yielding fewer neurons within developing cortical areas [ 49 ].…”
Section: The Potential Of Induced Pluripotent Stem Cells In Personali...mentioning
confidence: 99%
“…This approach supports the neurodevelopmental hypothesis of SZ, stating that the disruption of early brain development increases the risk of later manifest psychotic symptoms. Patient-derived iPSCs have proven to be a powerful tool in identifying SZ early neurodevelopmental defects, having revealed alterations in neuronal differentiation [ 45 , 48 , 49 ], migration capacity [ 39 , 43 ], neurite number and length [ 38 , 66 ], synaptic biology [ 47 , 49 , 50 ], connectivity [ 38 ], and neuronal activity [ 41 , 42 , 50 ].…”
Section: The Potential Of Induced Pluripotent Stem Cells In Personali...mentioning
confidence: 99%